Gene cloning, expression, and characterization of two endo-xylanases from Bacillus velezensis and Streptomyces rochei, and their application in xylooligosaccharide production - Zhang, Jing; Qin, Yan; Wang, Qingyan; Liu, Sijia; Zhou, Jin; He, Baoxiang; Liang, Xinquan; Xian, Liang; Wu, Junhua (Frontiers in Microbiology, 2023)
Endo-xylanase hydrolyzing xylan in cellulosic residues releasing xylobiose as the major product at neutral pH are desirable in the substitute sweeteners industry. In this study, two endo-xylanases were obtained from Streptomyces rochei and Bacillus velezensis. SrocXyn10 showed the highest identity of 77.22%, with a reported endo-xylanase. The optimum reaction temperature and pH of rSrocXyn10-Ec were pH 7.0 and 60°C, with remarkable stability at 45°C or pHs ranging from 4.5 to 11.0. rBvelXyn11-Ec was most active at pH 6.0 and 50°C, and was stable at 35°C or pH 3.5 to 10.5. Both rSrocXyn10-Ec and rBvelXyn11-Ec showed specific enzyme activities on wheat arabinoxylan (685.83 ± 13.82 and 2809.89 ± 21.26 U/mg, respectively), with no enzyme activity on non-xylan substrates. The Vmax of rSrocXyn10-Ec and rBvelXyn11-Ec were 467.86 U mg−1 and 3067.68 U mg−1, respectively. The determined Km values of rSrocXyn10-Ec and rBvelXyn11-Ec were 3.08 g L−1 and 1.45 g L−1, respectively. The predominant product of the hydrolysis of alkaline extracts from bagasse, corncob, and bamboo by rSrocXyn10-Ec and rBvelXyn11-Ec were xylooligosaccharides. Interestingly, the xylobiose content in hydrolysates by rSrocXyn10-Ec was approximately 80%, which is higher than most reported endo-xylanases. rSrocXyn10-Ec and rBvelXyn11-Ec could be excellent candidates to produce xylooligosaccharides at neutral/near-neutral pHs. rSrocXyn10-Ec also has potential value in the production of xylobiose as a substitute sweetener.